Student Problems In The Implementation Of The 2013 Curriculum With A Scientific Approach To Mathematics At MTs N 4 Cirebon - Ismaniar Hikmatusholikhah; Jamali; Arif Muchyidin (MASI Mandiri Edukasi, 2022)
This study aimed to explore student problems in implementing the 2013 curriculum with a scientific approach. This study uses a qualitative approach. Based on the results of the discussion, it can be concluded that the factors behind the VIII C grade students of MTs N 4 Cirebon related to the problem of not being able to respond to learning objectives with a scientific approach are: including internal factors, including; (1) lack of readiness to learn for each student, (2) at the stage of asking students are still shy and confused to ask questions related to material that has not been understood, and (3) at the stage of seeking information students feel confused to complete the questions/tasks given. Problems with external factors faced by students, including; (1) the way the teacher teaches that is felt to be in a hurry when delivering the material, (2) the lack of use of learning media by the teacher, and (3) the limitations of school facilities and infrastructure that are less supportive.